2021
DOI: 10.1002/adma.202006826
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of Alpha‐Germanium: A Covalent Diamond‐Like Structure

Abstract: 2D materials have opened a new field in materials science with outstanding scientific and technological impact. A largely explored route for the preparation of 2D materials is the exfoliation of layered crystals with weak forces between their layers. However, its application to covalent crystals remains elusive. Herein, a further step is taken by introducing the exfoliation of germanium, a narrow‐bandgap semiconductor presenting a 3D diamond‐like structure with strong covalent bonds. Pure α‐germanium is exfoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 21 publications
4
59
0
Order By: Relevance
“…Among the different crystallographic planes, the one with minimum bond strength is the least stable one under the shock wave and will induce the cleavage. [12] With the continuous sonication treatment, the cleavage tendency of the plane with lowest energy will be enhanced. (110), one of TiC crystallographic planes, is intersected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the different crystallographic planes, the one with minimum bond strength is the least stable one under the shock wave and will induce the cleavage. [12] With the continuous sonication treatment, the cleavage tendency of the plane with lowest energy will be enhanced. (110), one of TiC crystallographic planes, is intersected.…”
Section: Resultsmentioning
confidence: 99%
“…Ajayan's group demonstrated that nonlayered hematite can be exfoliated into 2D material "hematene." They attributed such exfoliation to the facet that direction perpendicular to {001} [12] has the highest broken bond density, so it is less stable, which results in preferable cleavage along [001] and [010] directions when hydrodynamic forces are applied. [13] More recently, 2D magnesium was fabricated after the crystals were treated in liquid nitrogen, which induced Mechanical exfoliation of bulk layered materials into atomic-layer thin nanosheets has become a general strategy to obtain 2D nanomaterials, which seems intuitively unsuitable for non-van der Waals crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Given these novel physical properties of germanium, uncovering the nanostructure and characteristics of the 2D Ge systems are timely.Unfortunately, the 3D diamond-like structure with strong covalent bonds impedes the layer-by-layer exfoliation, making it hard to generate ultrathin germanium with high crystallization quality by exfoliation. [8] Furthermore, the strong covalent bonds greatly hinder 2D anisotropic growth. Only some examples of nanoparticles [9][10][11] and ultrathin Ge(111) flakes were investigated.
…”
mentioning
confidence: 99%
“…e ., that high-aspect-ratio sheets can be prepared when the in-plane bonds are much stronger than those out-of-plane. This implies that both scission and delamination occur, and as such, the layered nature of the crystal is not a prerequisite and LPE can also be used to produce nanomaterials from nonlayered materials such as pyrite and germanium . However, in all these cases, the individual layers of the final nanomaterials are held together by strong in-plane covalent or coordination bonds.…”
mentioning
confidence: 99%